Sex-specific associations between daytime sleepiness, chronic diseases and mortality in obstructive sleep apnea - Covassin, Naima; Lu, Dongmei; St. Louis, Erik K.; Chahal, Anwar A.; Schulte, Phillip J.; Mansukhani, Meghna P.; Xie, Jiang; Lipford, Melissa C.; Li, Nanfang; Ramar, Kannan; Caples, Sean M.; Gay, Peter C.; et al. (Frontiers in Neuroscience, 2023)
Objective Excessive daytime sleepiness (EDS) is common in obstructive sleep apnea (OSA) and has been linked to adverse outcomes, albeit inconsistently. Furthermore, whether the prognostic impact of EDS differs as a function of sex is unclear. We aimed to assess the associations between EDS and chronic diseases and mortality in men and women with OSA. Methods Newly-diagnosed adult OSA patients who underwent sleep evaluation at Mayo Clinic between November 2009 and April 2017 and completed the Epworth Sleepiness Scale (ESS) for assessment of perceived sleepiness (N = 14,823) were included. Multivariable-adjusted regression models were used to investigate the relationships between sleepiness, with ESS modeled as a binary (ESS > 10) and as a continuous variable, and chronic diseases and all-cause mortality. Results In cross-sectional analysis, ESS > 10 was independently associated with lower risk of hypertension in male OSA patients (odds ratio [OR], 95% confidence interval [CI]: 0.76, 0.69–0.83) and with higher risk of diabetes mellitus in both OSA men (OR, 1.17, 95% CI 1.05–1.31) and women (OR 1.26, 95% CI 1.10–1.45). Sex-specific curvilinear relations between ESS score and depression and cancer were noted. After a median 6.2 (4.5–8.1) years of follow-up, the hazard ratio for all-cause death in OSA women with ESS > 10 compared to those with ESS ≤ 10 was 1.24 (95% CI 1.05–1.47), after adjusting for demographics, sleep characteristics and comorbidities at baseline. In men, sleepiness was not associated with mortality. Conclusion The implications of EDS for morbidity and mortality risk in OSA are sex-dependent, with hypersomnolence being independently associated with greater vulnerability to premature death only in female patients. Efforts to mitigate mortality risk and restore daytime vigilance in women with OSA should be prioritized.